2020
DOI: 10.1016/j.socscimed.2020.112793
|View full text |Cite
|
Sign up to set email alerts
|

The implications of ridehailing for risky driving and road accident injuries and fatalities

Abstract: The nature of transportation has fundamentally transformed in recent years with the rise of ridehailing providers such as Uber. Yet, few studies have examined whether there is an association between ridehailing and rates of road accident injuries, and virtually all of the existing studies focus on the exceptional case of the United States. In this study, we exploit differences in the timing of the deployment of Uber across Britain to test the association between the advent of Uber's ridehailing services and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 7 publications
2
29
0
Order By: Relevance
“…Ridesourcing services provide social equity benefits by providing increased access to transportation for older adults, particularly those that cannot drive [18]. They can also encourage a car-free lifestyle, reduce car ownership, and offer older adults more freedom of movement so they can rely less on friends or family to meet their needs for transportation [38,50,51].…”
Section: Positive Social Impactsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ridesourcing services provide social equity benefits by providing increased access to transportation for older adults, particularly those that cannot drive [18]. They can also encourage a car-free lifestyle, reduce car ownership, and offer older adults more freedom of movement so they can rely less on friends or family to meet their needs for transportation [38,50,51].…”
Section: Positive Social Impactsmentioning
confidence: 99%
“…Although ridesourcing services have created job opportunities for many people, there are concerns about unsecured labor rights, underemployment, and income instability. Labor rights are not secure in the ridesourcing industry and it may shift individuals away from secure employment to unsecured or footloose employment [50]. Moreover, the development of ridesourcing services has pushed many overqualified and educated people into underemployment.…”
Section: Negative Economic Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…A second limitation is related to the U.S.-centric focus of our study. To date, there has been very little research on the association between ridehailing and traffic fatalities focused on countries besides the United States (the few exceptions include recent studies of Chile, Great Britain, and South Africa), yet two of Uber's top five markets (London and Sao Paulo) are not in the United States and the majority of ridehailing trips worldwide occur outside of the United States, with an estimated 70 percent in Asia alone [25][26][27][28]. Hence, future research will need to examine the association between ridehailing and traffic fatalities beyond the United States before a full accounting of the impacts of ridehailing can be determined.…”
Section: Plos Onementioning
confidence: 99%
“…Researchers from Japan have evaluated the traffic safety of 46 prefectures in Japan and concluded that natural binding force, such as social rules and social capital, could reduce the dangerous driving behaviors [21]. Researchers from several European countries have deeply integrated police investigation data and accident reports and established an accident information collection and analysis system to analyze numerous traffic accidents in Europe [22][23][24][25][26]. It is found that the proportion of accidents caused by "vehicles driving off the roads" is up to 70% [27].…”
Section: Introductionmentioning
confidence: 99%